On the Tenacity of Christian Anti-Judaism - Lowe, Walter (Modern theology, 2006)
Joachim of Fiore's three ages of Father, Son and Spirit demonstrated that the supersessionist gambit Christianity had introduced against Judaism is a logic any successor can employ. Modernity (cf. modo, "now") is constituted by a relentless supersessionist logic; the modern issue is less supersessionism than a conflict of supersessionisms. Christianity has repeatedly overspiritualized God's "bodily covenant" with Israel (Wyschogrod). This distortive tendency is intensified in modernity by Christianity's anxiety that it too will appear old/"Jewish" vis-à-vis a new New Testament of infinite spiritual freedom (cf. Romanticism.) One corrective would be for Christianity to return to a more Jewish understanding of election.